(untitled) - 1969-; Kelly, Lynne; Nickolls, Leo (New York, 2019)
Twelve-year-old Iris and her grandmother, both deaf, drive from Texas to Alaska armed with Iris's plan to help Blue-55, a whale unable to communicate with other whales.
Keywords: People with disabilities; Fiction; Whales; Fiction; Fiction; Fiction; Grandmothers; Fiction; Automobile travel; Deaf; Automobile travel; Grandmothers; Juvenile fiction; Juvenile fiction; Whales; Juvenile fiction; People with disabilities; Juvenile fiction; Deaf; Juvenile fiction